Nature-based tourism operators’ perceptions and adaptation to climate change in Hwange National Park, Zimbabwe - Mushawemhuka, William; Rogerson, Jayne M.; Saarinen, Jarkko (Bulletin of Geography. Socio-economic Series, 2018)
Climate and weather are important resources for tourism. In particular, nature-based tourism activities and operations are largely dependent on and affected by environmental conditions and changes. Due to the significant socio-economic role of the nature-based tourism and the tourism industry, in general, in the region of southern Africa it is important to understand the dynamics between the industry and climate change. A key aspect of this understanding are perceptions and adaptation preparedness of tourism operators towards the estimated impact of climate change. There is a dearth of empirical studies on climate change perceptions and adaptation in nature-based tourism operations across southern Africa and specifically from Zimbabwe. This research gap is addressed in this article which provides an exploratory analysis of the nature of climate change adaptation practices occurring in southern Africa using evidence from Hwange National Park, Zimbabwe.